The Marajoara Wrestling: between vernacular practice and institutionalization - Coelho, Leonardo; Valério, Pedro Henrique Martins; Barreira, Cristiano Roque Antunes (Revista de Artes Marciales Asiáticas, 2025)
The Marajoara Wrestling is a traditional grappling and throwing fight, typical of Marajó Island in the state of Pará, northern Brazil. The sport is going through a process of expansion through competitions and tournaments. The objective of this research is to understand elements and experiences specific to the institutionalization process in the Marajoara Wrestling through an empirical-phenomenological investigation. It is an exploratory, qualitative study, anchored in interviews and supported by ethnographic procedures to produce a broad understanding of the cultural contexts of the Marajoara Wrestling, as well as its practical and technical objectivity. The results are divided into three parts: Marajoara Wrestling and Tradition in Techniques; Marajoara Wrestling and its institutionalization; Marajoara Wrestling versus Agarrada. Understanding the phenomena present in Marajoara Wrestling makes it possible to understand the tensions in the process of institutionalizing the sport. Understanding these tensions enables an interventionist and educational role in Marajoara Wrestling, which is of interest applied to both Physical Education and Sports Psychology.